Comparing the maximal aerobic speed assessed with laboratory and field tests in soccer players - Erkan Akdogan; Cihan Aygun; Hayriye Cakir-Atabek; Ali Onur Cerrah (Ozlem Book Center, 2023)
The aim of the study was to compare the maximal aerobic speed (MAS) obtained from the VAM-EVAL and Yo-Yo intermittent recovery test (YYIR1), with an incremental (1km.h-1 per min) treadmill test in soccer players. Eighteen amateur male soccer players, were evaluated with the following tests: a) a treadmill test to directly determine values of maximal oxygen uptake (VO2max) and MAS (Treadmill); b) an indirect VAM-EVAL Test; c) an indirect YYIR1. The results demonstrated that the last speed, distance, and test duration values are significantly different among the tests (p<0.05)]. The highest MAS value was recorded during the treadmill test (17.10±1.38 km.h-1) which was significantly different from YYIR1 and VAM-EVAL tests (15.82±0.66 and 14.33±0.69 km.h-1, respectively; p<0.001).  The analysis also showed that treadmill MAS value was significantly correlated with YYIR1 MAS (r = 0.656) and VAM-EVAL MAS values (r =0.625), also YYIR1 MAS value was significantly correlated with VAM-EVAL MAS value (r=0.662). It was concluded that the MAS and the VO2max values are significantly different among YYIR1, VAM-EVAL and selected treadmill protocol, and support the idea that they should not be used interchangeably. From a practical perspective, MAS seems to be more important for coaches than VO2max. Both laboratory and field tests can be useful for assessing MAS; however, field tests should be preferred for training purposes.